METHODS OF MANAGING THE FINANCIAL SITUATION OF BANKS - Jaloliddinovich , Rakhmatov Azizjon (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
Today, it is an urgent problem to study the methods of managing the financial situation of our commercial banks and introduce innovations. The article focuses on the methods of managing the financial situation of commercial banks and gives conclusions.